IMPLIKASI DAN MEKANISME EKSEKUSI OBJEK JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NO.18/PUU-XVII/2019 DALAM HAL DEBITUR WANPRESTASI - Meiliana, Brigita Cindy; Suryono, Arief (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article aims to find out the legal implications of the Constitutional Court Decision No.18 / PUU-XVII / 2019 and the mechanism for the execution of fiduciary object guarantees after the Constitutional Court Decision No.18 / PUU-XVII / 2019. This type of research is normative with the nature of applied and prescriptive research. Based on the results of research and discussion, the most important implications are the reduced executive power of fiduciary certificates, the elimination of the parate execution mechanism, and inefficiency in handling fiduciary guarantee disputes. Meanwhile, the mechanism is longer and more complicated.